Experimental evaluation of a compact two-phase cooling system for high heat flux electronic packages. (25th December 2019) - Hou, Fengze; Wang, Wenbo; Zhang, Hengyun; Chen, Cheng; Chen, Chuan; Lin, Tingyu; Cao, Liqiang; Zhang, G.Q.; Ferreira, J.A.
Highlights: The system can dissipate over 380 W/cm 2 while keeping chip temperature at 90 °C. Heat flux that the system could dissipate decreases with heat source area. The downstream super heater can improve the thermal performance. Increasing differential pressure can improve the heat dissipation capacity. Abstract: In this work, an experimental study on the aluminum plate fin evaporator based on a compact two-phase cooling system for high heat flux electronic packages is presented. Single-chip and multi-chip wire-bonded thermal test vehicles (TTVs) were fabricated and assembled in the PCB grooves designed to emulate high heat flux sources. The issue of heat dissipation was addressed by applying the evaporator to the TTVs, respectively, to evaluate their thermal characteristics. It is found that, the evaporator system could dissipate over 380 W/cm 2 for the TTV1 while maintaining its temperature at about 90 °C. As the effective heat source area and thermal design power (TDP) increased, the maximum heat flux that the system could dissipate decreased given the same chip temperature rise. Furthermore, the addition of a second evaporator and heat source following the main evaporator, increased the dissipation of the system. As a result, an increase of 48 W/cm 2 in heat removal capacity was observed in our test system. Finally, the effect of the differential pressure between the condenser and the evaporator was investigated. The increase in the differential pressure could improve the heat dissipation capacity of the two-phase cooling system. The temperature of the TTV2 dropped by 19 °C when the differential pressure increased by 2.7 bar. It can be concluded that the compact two-phase cooling system is a promising solution for removing heat from high heat flux electric packages.